Mulheres leitoras : representações iconográficas na pintura de Almeida Júnior 1890-1900) - Miyoshi, Simone Cléa dos Santos (2015)
This research aimed to contribute with the studies of representations and images of readers women. For this, it was necessary to make an approach about the women history, the education history and Art history, an also, the understanding of the studied period. The time, and geographic frame comprehended the years 1890 to 1900, at the state of São Paulo; the sources used were the paintings of Jose Ferraz de Almeida Junior, a painter who was born in Sao Paulo. The paint, as source for the writing of the education history, was used because the importance of its pictorial registration about the theme of readers women. They were created in a singular moment of the Brazil politic history, when the capital of the state of São Paulo was trying to grow in front of the nation as a model of civilization and progress. It was aimed, also, to enlarge the knowledge about the role of these images related with the education history, trying to understand the place of the woman in this relation, understand how these images could interfere in its constitution as a subject, educating the look, not just the women s look, but also the men s, children s, and of a hole generation and society that kept contact with them.